Influence of the Ethanol Lure and Concentration on Captures of Ambrosia Beetles in Tree Fruits and Ornamentals - Govindaraju, Ramkumar; Hayter, Jensen; Chong, Juang Horng; Del Pozo‐Valdivia, Alejandro I.; Cottrell, Ted E.; Walgenbach, James F.; Scheyer, Thomas W.; Blaauw, Brett R.; Reding, Michael E.; Ranger, Christopher M.; Joseph, Shimat V. (Journal of applied entomology (1986), 2025)
ABSTRACT Xylosandrus crassiusculus (Motschulsky) and Xylosandrus germanus (Blandford) (Coleoptera: Curculionidae: Scolytinae) are major ambrosia beetle pests in tree nut and fruit orchards and ornamental nurseries in the eastern United States (USA). Ethanol‐baited bottle traps and ethanol‐infused tree stem sections (i.e., bolts) have been used to monitor ambrosia beetles, but limited studies exist on the influence of ethanol‐lure release rate on ambrosia beetle trap captures and bolt attacks. We designed this study to compare low‐release (LR) and high‐release (HR) ethanol lures in bottle traps for capturing invasive ambrosia beetles. We also compared beetle attacks among bolts pre‐soaked in ethanol solutions of low (10%) and high (90%) concentrations and bolts cored and filled with the same low and high ethanol concentrations. In 2022, experiments were conducted in ornamental nurseries and apple, peach, or pecan orchards in five USA states. Higher numbers of X. crassiusculus and X. germanus were captured in bottle traps baited with the HR ethanol lure compared to the LR lure at most of the study sites. More attacks per bolt by X. crassiusculus and X. germanus were observed at most sites on pre‐soaked and filled bolts with 90% compared to 10% solutions of ethanol. Bolts soaked in low (10%) ethanol solutions sustained more attacks from both X. crassiusculus and X. germanus than cored bolts filled with low ethanol. These results will assist with monitoring the flight activity of invasive ambrosia beetles within nut, fruit, and ornamental tree crops.